2001
DOI: 10.1128/mcb.21.20.7010-7019.2001
|View full text |Cite
|
Sign up to set email alerts
|

MSY2 and MSY4 Bind a Conserved Sequence in the 3′ Untranslated Region of Protamine 1 mRNA In Vitro and In Vivo

Abstract: The mouse Y-box proteins MSY2 and MSY4 are members of a protein family found in prokaryotes and eukaryotes that contain the highly conserved cold-shock domain (CSD). This 67-to 80-amino-acid (aa) nucleic acid binding domain is 43% identical from Escherichia coli to humans, contains the RNP1 and RNP2 RNA binding motifs, and forms a five-stranded antiparallel ␤-barrel structure (36). The prokaryotic members of this family, such as major cold-shock protein CspA in E. coli, are about 70 aa in length and are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 39 publications
3
88
0
Order By: Relevance
“…Accompanying these changes is the tightly timed expression of many testicular genes. In male mice, MSY2 and MSY4 are abundant in meiotic and early haploid cells (9,15,18), where they package germ cell mRNAs (12,25). The high levels of CSD proteins in murine spermatocytes may Giorgini and colleagues (13) recently showed that overexpression of MSY4 in mouse germ cells severely disrupts spermatogenesis, suggesting the importance of maintenance of proper levels of CSD proteins in the germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying these changes is the tightly timed expression of many testicular genes. In male mice, MSY2 and MSY4 are abundant in meiotic and early haploid cells (9,15,18), where they package germ cell mRNAs (12,25). The high levels of CSD proteins in murine spermatocytes may Giorgini and colleagues (13) recently showed that overexpression of MSY4 in mouse germ cells severely disrupts spermatogenesis, suggesting the importance of maintenance of proper levels of CSD proteins in the germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…YB-1 and MSY4 proteins can also bind to non-B form DNA elements upstream from the human gamma globin genes, the c-myc gene, and the Vegf gene (references 8 and 16 and references therein). Finally, mouse CSD proteins have been shown to possess similar nucleotide sequence preferences for RNA binding in vitro (12).…”
mentioning
confidence: 99%
“…YB-1 protects from cleavage two sequences of the regulatory element of its own mRNA (nt 1133 to 1145 and 1165 to 1172), AGUCAUCCAACAA and UCCAGCAA, that include 8-nt motifs (underlined) differing from each other by only one nucleotide in the fifth position (A in the former and G in the latter). The motif UCCAG/ACAA described here almost coincides with the specific binding motif UCCAUCA for the mice homolog of YB-1, MSY2/MSY4 (14). Inasmuch as YB-1 protects from cleavage two sites of the YB-1 mRNA 3ЈUTR regulatory element, it is most likely that two YB-1 molecules interact with this element.…”
mentioning
confidence: 95%
“…Y-box factors can bind nucleic acids in vitro by targeting sequences with central C(N)CAUC motifs in RNA (35). Sequence analysis revealed that all known human p21 transcripts have two such potential binding sites in their 3′-UTR (Fig.…”
Section: Cell Survival During Proinflammatory Signaling and Stress Ismentioning
confidence: 99%